2016
DOI: 10.1007/s00360-016-0992-2
|View full text |Cite
|
Sign up to set email alerts
|

Torso, a Drosophila receptor tyrosine kinase, plays a novel role in the larval fat body in regulating insulin signaling and body growth

Abstract: Torso is a receptor tyrosine kinase whose localized activation at the termini of the Drosophila embryo is mediated by its ligand, Trunk. Recent studies have unveiled a second function of Torso in the larval prothoracic gland (PG) as the receptor for the prothoracicotropic hormone, which triggers pupariation. As such, inhibition of Torso in the PG prolongs the larval growth period, thereby increasing the final pupa size. Here, we report that Torso also acts in the larval fat body, regulating body size in a mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
2
11
1
Order By: Relevance
“…One of the more unexpected findings of this study is that Drosophila PTTH appears to act autonomously for regulating E biosynthesis within the PG, whereas a previous study demonstrated that PTTH in the hemolymph acts non-autonomously, and in a Torso-dependent manner, to regulate larval light avoidance (Yamanaka et al, 2013b). In addition, a recent study showed that Torso expression in the fat body is required for proper insulin signaling and body size control although the ligand involved was not identified (Jun et al, 2016). Since PTTH reaches the PG through the circulatory system in Lepidoptera, it is unlikely that there is an intrinsic functional need to regulate E biosynthesis through direct innervation of the PG, and indeed we found that overexpression of PTTH in the fat body was able to rescue the developmental delay and body size phenotypes of Ptth null mutants (data not shown).…”
Section: Autonomy Versus Non-autonomy Of Ptth Signalingcontrasting
confidence: 54%
“…One of the more unexpected findings of this study is that Drosophila PTTH appears to act autonomously for regulating E biosynthesis within the PG, whereas a previous study demonstrated that PTTH in the hemolymph acts non-autonomously, and in a Torso-dependent manner, to regulate larval light avoidance (Yamanaka et al, 2013b). In addition, a recent study showed that Torso expression in the fat body is required for proper insulin signaling and body size control although the ligand involved was not identified (Jun et al, 2016). Since PTTH reaches the PG through the circulatory system in Lepidoptera, it is unlikely that there is an intrinsic functional need to regulate E biosynthesis through direct innervation of the PG, and indeed we found that overexpression of PTTH in the fat body was able to rescue the developmental delay and body size phenotypes of Ptth null mutants (data not shown).…”
Section: Autonomy Versus Non-autonomy Of Ptth Signalingcontrasting
confidence: 54%
“…6B; Geminard et al 2009;Rajan & Perrimon, 2012;Sano et al 2015;Delanoue et al 2016;Koyama & Mirth 2016). Interestingly, a recent study found that knocking down tor specifically in the fat body led to a decreased body size, leading the authors to suggest that Tor acts in the fat body to influence insulin signalling via an unknown mechanism (Jun et al 2016). Given the key role of Tsl in the regulation of Tor activity during early embryogenesis, it is therefore possible that Tsl acts in the Tor pathway in the fat body.…”
Section: Discussionmentioning
confidence: 99%
“…Given the key role of Tsl in the regulation of Tor activity during early embryogenesis, it is therefore possible that Tsl acts in the Tor pathway in the fat body. However, fat body-specific knockdown of tor does not result in a developmental delay (Jun et al 2016), thus this would seem unlikely to be the only role for Tsl in regulating growth and developmental transitions. In addition, experiments that we have performed to detect Tsl or knockdown its expression in the fat body have not provided any evidence of Tsl expression or function in this tissue.…”
Section: Discussionmentioning
confidence: 99%
“…6B; Geminard et al 2009;Rajan & Perrimon, 2012;Sano et al 2015;Delanoue et al 2016;Koyama & Mirth 2016). Interestingly, a recent study found that knocking down tor specifically in the fat body led to a decreased body size, leading the authors to suggest that Tor acts in the fat body to influence insulin signalling via an unknown mechanism (Jun et al 2016). Given the key role of Tsl in the regulation of Tor activity during early embryogenesis, it is therefore possible that Tsl acts in the Tor pathway in the fat body.…”
Section: Discussionmentioning
confidence: 99%